Mental health and burnout levels of early childhood education pedagogical teams in Chile - Fuentes-Vilugrón, Gerardo; Baeza-Vargas, Yasna; Fuentes-Fuentes, Daniela; Ortiz-Peña, Daniela; Rojas-Estrada, Darlyn; Sandoval-Obando, Eduardo; Arriagada-Hernández, Carlos; Caamaño-Navarrete, Felipe; Etchegaray-Pezo, Paulo; Castellanos-Alvarenga, Luis Mario (Frontiers in Education, 2025)
IntroductionMental health is a state of complete wellbeing that includes people’s cognitive, affective, and behavioral aspects. This means that an individual with low levels of depression, anxiety, and stress can function optimally in their daily life, contributing to the community and enjoying and creating meaningful relationships with their peers and environment. The purpose of the study was to determine the levels of stress, anxiety, and depression along with the levels of burnout manifested by Chilean preschool education professionals.MethodA quantitative, non-experimental, correlational design was applied. A purposive sample of 560 preschool teachers and assistants participated. Data were collected using the Depression Anxiety and Stress Scale (DASS-21) and the Maslach Burnout Inventory (MBI). Analyses included descriptive and inferential statistics.ResultsParticipants exhibited low levels of stress, anxiety, and depression. However, emotional exhaustion and depersonalization showed positive correlations with all three mental health indicators. Conversely, personal accomplishment was negatively correlated with them. Structural equation modeling revealed that anxiety mediates the relationship between burnout and depressive symptoms, with emotional exhaustion having the greatest impact.DiscussionThese findings underscore the importance of reinforcing psychological and socio-emotional support for preschool education teams. Strengthening professional wellbeing is critical not only for educators’ health but also for enhancing the quality of early childhood education.